Integrating of Green Environment in Modern Property Market - Md Amanat Ullah; Seow Ta Wee; Md Mahadi Hasan; Siti Zaitun Osman; G M Faysal (STIM LASHARAN JAYA MAKASSAR, 2019)
The property demand and value habitually based on environmental facilities at the surrounding of the apartment complex. Among the educated and average income group of people having a high request for that housing existing a natural green environment, entertainment environment and health & safety environment. Most of them gives the priority on environmental facilities instead of price as a consequence the property demand and value rise simultaneously. Malaysian condominium developers can attract the target customers to achieve the target sales by green marketing with strategic advertising. Currently, many developers are practising to add the environmental elements in their marketing strategy. As a consequence, the foreign investment is increasing in the housing industries, and the developer’s business is becoming successful field not only Malaysia but also Singapore, Australia, UAE and so one.